2017
DOI: 10.1111/jsap.12637
|View full text |Cite
|
Sign up to set email alerts
|

Malignant anal sac melanoma in dogs: eleven cases (2000 to 2015)

Abstract: Dogs in this case series had a guarded to poor prognosis regardless of treatment. Ten of 11 dogs were euthanased due to local or distant disease progression. Only 1 of 11 dogs was alive one year after diagnosis. An understanding of tumour behaviour in this location could lead to improved survival times with earlier diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Mean age at diagnosis is around 10–11 years of age, and several studies have identified breeds more prone to develop this oral form, such as poodles, golden and Labrador retrievers, Rottweilers, Yorkshire terrier, cocker spaniels, chow-chows, Scottish terriers, and daschunds (Figure 4A) [34,38,39,40,42,43,44]. Other mucosal sites comprise the anorectal region [45], intestines [46], and nasal cavity, but these entities are very rare in dogs [47,48,49].…”
Section: Canine Mucosal Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Mean age at diagnosis is around 10–11 years of age, and several studies have identified breeds more prone to develop this oral form, such as poodles, golden and Labrador retrievers, Rottweilers, Yorkshire terrier, cocker spaniels, chow-chows, Scottish terriers, and daschunds (Figure 4A) [34,38,39,40,42,43,44]. Other mucosal sites comprise the anorectal region [45], intestines [46], and nasal cavity, but these entities are very rare in dogs [47,48,49].…”
Section: Canine Mucosal Melanomamentioning
confidence: 99%
“…Some cases of intranasal or anal sac melanoma have been reported, but these are rare and prognosis is poor. In a recent study, 12 anal sac melanoma cases were treated with surgery most of the time with or without adjuvant chemotherapy, and 10/12 dogs experienced local recurrence or metastasis to regional lymph nodes, penis, or lungs [45].…”
Section: Canine Mucosal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Apocrine gland anal sac adenocarcinoma (AGASACA) is a malignant epithelial neoplasm comprising 2% of all canine skin tumors and 17% of perianal malignancies, with the remaining tumor types consisting of perianal adenoma or adenocarcinoma, squamous cell carcinoma, and malignant melanoma [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. A clinical staging scheme was proposed and then tested in a study of 130 dogs with naturally occurring diseases [ 5 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common diseases of the canine anal sacs and glands include impactions, neoplasia, inflammation, and infection 4–6 . Apocrine gland anal sac adenocarcinoma is the most commonly reported neoplasia of the anal sacs and glands, with other tumors, including squamous cell carcinoma and malignant melanoma, reported less frequently 6–8 . Computed tomography is widely used to determine the size of the tumors of the anal glands 9 .…”
Section: Introductionmentioning
confidence: 99%